Ремінісценції японської гравюри укійо-е в сучасній художній практиці України - Ожога-Масловська, Алла Валентинівна (АРТПРОСТІР, 2015)
У статті розглядаються твори сучасних українських митців у контексті японської гравюри укійо-е. Апеляція художників України до японської спадщини простежується у використанні цитат з відомих графічних творів, перекладі окремих мотивів на мову інших видів мистецтва та матеріалів, запозиченні тиражованих у гравюрі образів, застосуванні художніх принципів та прийомів укійо-е. Стаття побудована на матеріалах музейних та приватних колекцій.Ключові слова: японська гравюра укійо-е, сучасне українське мистецтво, ремінісценція, пара-лельна перспектива, простір, образотворча цитата, інтерпретація.Ожога-Масловская А.В. Реминисценции японской гравюры укие-э в современной художественной практике УкраиныВ статье рассматриваются произведения современных украинских художников в контексте японской гравюры укие-э. Апелляция художников Украины к японскому наследию прослеживается в использовании цитат из известных графических произведений, переводе отдельных мотивов на художественный язык других видов искусства и материалов, заимствовании тиражируемых в гравюре образов, применении художественных принципов и приемов укие-э. Статья построена на материалах музейных и частных коллекций.Ключевые слова:японская гравюра укие-э, современное украинское искусство, реминисценция, параллельная перспектива, пространство, изобразительная цитата, интерпретация.Ozhoga-Maslovska A.Reminiscences of Japanese Ukiyo-e prints in modern art practice in UkraineThe article deals with the works of contemporary Ukrainian artists in the context of Japanese Ukiyo-e prints. The appeal to Japanеsе cultural heritage of the artists of Ukraine can be seen in the use of quotations from prominent graphic works, the transferring of individual motifs of artistic language onto different art forms and materials, and the borrowing and replication of engraved images, applied using the artistic principles and techniques of Ukiyo-e. The article is based on the materials of museums and private collections.Key words: Japanese Ukiyo-e prints, contemporary art of Ukraine, reminiscence, parallel perspective, space, iconic quote, interpretation.